Microflora associated with experimental root surface caries in humans. - Nyvad, B (1990)
This study describes the microflora from actively progressing root surface caries lesions, in which mineral loss had been determined by quantitative microradiography. The caries lesions were produced experimentally in root surface specimens from human molars inserted in lower partial dentures carried for 3 months by six elderly individuals. A total of 780 bacterial isolates were identified from 13 plaque samples, collected with a punch technique, and six dentin samples. The composition of the microflora showed distinct individual differences. The microflora from plaque samples associated with the highest mineral loss was dominated by either Actinomyces viscosus or a combination of mutans streptococci (serotypes c, d, and f) and Lactobacillus species (L. casei and L. brevis). Plaque from root surfaces with less pronounced mineral loss harbored a more complex microflora comprising gram-positive rods, mutans streptococci, Streptococcus mitis biovar 1, Veillonella spp., gram-negative rods, and low numbers of lactobacilli. In the latter samples, individual variations in the proportions of mutans streptococci (serotypes c, d, and g), Actinomyces species (A. viscosus and A. naeslundii), and Veillonella parvula biotypes were observed. These findings suggest that certain species or combinations of species are more cariogenic than others and that dominance of single acidogenic species in particular is conducive to high caries activity.